2016
DOI: 10.3892/ijo.2016.3435
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA analysis of breast ductal fluid in breast cancer patients

Abstract: Recent studies suggest that microRNAs show promise as excellent biomarkers for breast cancer; however there is still a high degree of variability between studies making the findings difficult to interpret. In addition to blood, ductal lavage (DL) and nipple aspirate fluids represent an excellent opportunity for biomarker detection because they can be obtained in a less invasive manner than biopsies and circumvent the limitations of evaluating blood biomarkers with regards to tissue of origin specificity. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…The first study focusing on milk microRNAs was only reported in 2010 (Hata et al., ; Kosaka et al., ) and opened a very new field of research focused on milk microRNAs. From then on, a number of studies have focused on investigating milk microRNAs profiles in various conditions including mammary gland infections (Sun et al., ), breast cancer (Do Canto et al., ; Gu et al., ; Pigati et al., ), lactation periods (Hou et al., ; Na et al., ; Xi et al., ), milk processing (Howard et al., ; Oh et al., ), and digestion (Benmoussa et al., ; Kahn et al., ; Liao, Du, Li, & Lonnerdal, ).…”
Section: Micrornas In Milkmentioning
confidence: 99%
See 2 more Smart Citations
“…The first study focusing on milk microRNAs was only reported in 2010 (Hata et al., ; Kosaka et al., ) and opened a very new field of research focused on milk microRNAs. From then on, a number of studies have focused on investigating milk microRNAs profiles in various conditions including mammary gland infections (Sun et al., ), breast cancer (Do Canto et al., ; Gu et al., ; Pigati et al., ), lactation periods (Hou et al., ; Na et al., ; Xi et al., ), milk processing (Howard et al., ; Oh et al., ), and digestion (Benmoussa et al., ; Kahn et al., ; Liao, Du, Li, & Lonnerdal, ).…”
Section: Micrornas In Milkmentioning
confidence: 99%
“…In milk, microRNA expression was related to mammary gland conditions, including infections (Iannaccone et al., ; Lai et al., , ; Sun et al., ), cancer (Decmann et al., ; Do Canto et al., ; Hesari et al., ), pregnancy and lactation status (Carney et al., ; Perri et al., ; Schanzenbach et al., ), and maternal diet (Chen et al., ). Therefore microRNAs in milk were studied for their potential as biomarkers (Gustafson, Tyryshkin, & Renwick, ; Melnik & Schmitz, ) such as quality controls of commercial milk (Oh et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…They showed that NAF is metabolically distinct from matched plasma samples which supports the theory that the cellular environment (tumor microenvironment) is more directly mirrored in breast biofluids (DL and NAF). We have recently identified a panel of microRNAs that are differentially expressed in ductal fluid from breasts with tumors compared to paired ductal fluid samples from the contralateral normal breast (19), further substantiating the importance of a more direct analysis of the tumor microenvironment and the potential for biomarker development using ductal fluid obtained in a non-invasive or minimally invasive approach. Here, we report the first metabolomic analysis of breast ductal fluid samples obtained from 43 patients with unilateral breast cancer.…”
Section: Introductionmentioning
confidence: 77%
“…However, serum and plasma can also be monitored as significant differences were found in miRNA levels between breast cancer patients and controls. Only as recently as 2016 has DL fluid been studied for potential use in miRNA detection for cancers [19].…”
Section: Introductionmentioning
confidence: 99%